Genetic Algorithm-Based Optimization of a Miniature Wearable Fractal Patch Antenna for Medical Purposes - Mahesh, D. S.; Naveen, K. B. (SN computer science, 2024)
This paper presents the design, simulation, optimization and implementation of a Fractal antenna, genetic algorithm (GA) was chosen for fractal antenna optimization. The fractal antenna considered here was fed by a 1.59 mm diameter coaxial cable, the location of feeding was varied by genetic algorithm (GA). The length and number of sides of the fractal antenna were also changed using the genetic algorithm (GA). Finding a set of settings that would enhance the antenna's performance was the optimization's goal. The parameters considered were return loss (reflection coefficient S11) and the voltage standing wave ratio (VSWR).The GA yielded a design with return loss (S 11 ) of − 27.37 dB and VSWR of 1.11 at 2.4 GHz. The entire antenna dimensions will be approximately (5 cm × 5 cm). The substrate used is FR4 (flame retardant) epoxy. There was strong agreement between the measurements from the antenna’s (fabrication) manufacturing and simulation for the operational frequencies and desirable performance in gain, bandwidth and VSWR (voltage standing wave ratio) parameters. The VSWR achieved values was lower than 1.4 for the frequencies used. Additionally, the simulations portray a broad radiation pattern and shows good gain and directivity. The antenna which was fabricated was tested using Anechoic Chamber and network analyser. The antenna which is tested in anechoic chamber was used in wearable health care application due to its small size. At the transmitter side we used temperature and pulse reading sensors to collect physiological information like body temperature and heart rate from the patient, these sensors were connected to Arduino microcontroller then to transmit these physiological information, NRF24L01 trans receiver module along with our fabricated 15th generation GA optimised Fractal antenna was used, which is connected to Arduino microcontroller. At the receiver side we received the physiological information using, NRF24L01 Trans receiver module along with our fabricated 15th generation GA optimised Fractal antenna connected to Arduino microcontroller.